Torture and Theology of the Cross - Hoffmeyer, John F. (Dialog, 2008)
A theology of the cross must (1) connect Christ's cross with the reality of torture, and (2) differentiate misuse of Christ's crucifixion from its power in the struggle against torture. To meet these tasks, a theology of the cross needs to (1) refuse to separate Christ's crucifixion from his life and resurrection, and (2) recognize that the crucified Christ can only be understood in relation to all Christ's suffering sisters and brothers.